How an energy drink affects planarians: a high school investigation. (2nd October 2019) - Miles, Rhea; Misra, Shinjini; Miles, Kyra; Doherty, Caroline
Abstract: Many students consume energy drinks without knowing or thinking about the adverse side effects. The purpose of this article is to share student procedures and results after testing the effects of a popular energy drink, Red Bull, on Dugesia Dorotocephala planarians (flatworms). Planarians are animals with neurotransmitters systems that are similar to mammals and teachers can use these flatworms in the classroom to teach students about the harmful effects of drug use. In this article, we discuss how a teacher uses the 5E model to assist 9–12 grade high school student participants of the Science Education Against Drug Abuse Program (SEADAP) with the design and development of their science fair project. This article also focuses on how there are statistically significant differences in planarian motility, stereotypy, and time spent in the light after conditioned place preference in Red Bull and its active chemical ingredients.